Environmental Security and Water Wars in Africa: A Reflection on Nigeria - ENOCH NDEM OKON; VICTOR OJAKOROTU (African Journal of Governance and Development, 2021)
Depletion of fresh water arising from climate change and exploitation of mineral resources in African countries have contributed to violent conflicts on the continent. This study seeks to unveil the link between environmental security and water wars in the oil rich Niger Delta region and shrinking Lake Chad in the North East of Nigeria as archetypes on the continent. It depends mainly on secondary data which are qualitatively presented and analyzed. The study discovers that the exploration and exploitation of oil in the Niger Delta region of Nigeria depletes fresh water due to pollution; and the shrinking of Lake Chad by climate change forces the herdsmen to migrate southward to Benue and other river plains for pasture. This leads to herdsmen/farmers’ conflict. These conflicts exacerbate environmental insecurity and its inherent consequences in a cyclical manner, thereby perpetuating environmental security deficit in the country. This study therefore recommends the cleaning of oil and industrial polluted waters and the adoption of best global practices in the extractive industry across Nigeria and the continent. Besides, Nigeria must invest more in the construction of irrigation facilities; as well as evolving policies that would regenerate the Lake Chad and the grassland in the North.